# 285hw10 - HW 10 1 Sec 9.3 5 We have f(t = 0 if t 2(0 1 f(t...

This preview shows pages 1–8. Sign up to view the full content.

f 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
a 0 = 2 3 Z 3 0 f ( t ) dt = 2 3 Z 2 1 dt = 2 3 t j 2 1 = 2 3 : a n = 2 3 Z 2 1 cos n&t 3 dt = 2 3 & 3 n& & sin n&t 3 j 2 1 = 2 n& (sin 2 &n 3 ± sin &n 3 ); n = 6 k = ) a n = 2 n& (sin 0 ± sin 0) = 0 ; n = 1 + 6 k = ) a n = 2 n& & sin 2 & 3 ± sin & 3 ± = 0 ; n = 2 + 6 k = ) a n = 2 n& & ± sin 2 & 3 ± sin 2 & 3 ± = 2 n& & ± 2 & p 3 2 ! = ± 2 p 3 n& ; n = 3 + 6 k = ) a n = 2 n& (sin 0 ± sin 0) = 0 ; n = 4 + 6 k = ) a n = 2 n& & sin 2 & 3 ± ( ± sin 2 & 3 ) ± = 2 n& & 2 & p 3 2 = 2 p 3 n& ; n = 5 + 6 k = ) a n = 2 n& ² ± sin & 3 ± ( ± sin & 3 ) ³ = 0 : Thus f ( t ) = 1 3 ± 2 p 3 & ´ 1 2 cos 2 &t 3 ± 1 4 cos 4 &t 3 + 1 8 cos 8 &t 3 ± ::: µ : 2 case: sine series. See the sketch. 2
Thus b n = 2 3 Z 3 0 f ( t ) sin n&t 3 dt = 2 3 Z 2 1 sin n&t 3 dt = & 2 3 ± 3 n&t ± cos n&t 3 j 2 1 = & 2 n& & cos 2 &n 3 & cos n& 3 ± ; n = 6 k = ) b n = & 2 n& (cos 0 & cos 0) = 0 ; n = 1 + 6 k = ) b n = & 2 n& ² & cos & 3 & cos & 3 ³ = 2 n& ; n = 2 + 6 k = ) b n = & 2 n& ² & cos & 3 & ( & cos & 3 ) ³ = 0 ; n = 3 + 6 k = ) b n = & 2 n& (cos 0 & cos & ) = & 4 n& ; n = 4 + 6 k = ) b n = & 2 n& ² & cos & 3 & ( & cos & 3 ) ³ = 0 ; n = 5 + 6 k = ) b n = & 2 n& ² & cos & 3 & cos & 3 ³ = 2 n& : f ( t ) = 2 & ´ sin &t 3 & 2 3 sin &t + 1 5 sin 5 &t 3 + ::: µ : 2. Sec. 9.3: 15. We have x 00 + 2 x = t;x 0 (0) = x 0 ( & ) = 0 : We need to &nd 3

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
the cosine series of f ( t ) = t: a 0 = 2 & Z & 0 tdt = 2 & & 1 2 t 2 j & 0 = 1 & & & 2 ± 0 ± = &: a n = 2 & Z & 0 t cos ntdt = 2 n& Z & 0 td sin nt = 2 n& ² t sin nt j & 0 ± Z & 0 sin ntdt ³ = 2 n& & 1 n & cos nt j & 0 = 2 n 2 & (cos n& ± cos 0) = 2 n 2 & (( ± 1) n ± 1) : Thus f ( t ) = & 2 ± 2 & 1 X n =1 1 ± ( ± 1) n n 2 cos nt: Now we are looking for the solution in the form x ( t ) = A 0 2 + 1 X n =1 A n cos nt; then x 0 ( t ) = ± 1 X n =1 nA n sin nt; x 00 ( t ) = ± 1 X n =1 n 2 A n cos nt: So we get ± 1 X n =1 n 2 A n cos nt + A 0 + 2 1 X n =1 A n cos nt = & 2 ± 2 & 1 X n =1 1 ± ( ± 1) n n 2 cos nt; whence A 0 = & 2 ; 2 A n ± n 2 A n = ± 2 &n 2 (1 ± ( ± 1) n ) = ) A n = 2 (1 ± ( ± 1) n ) &n 2 ( n 2 ± 2) : Thus x ( t ) = & 4 + 2 & 1 X n =1 1 ± ( ± 1) n n 2 ( n 2 ± 2) cos nt: 4
3. Sec. 9.3: 19. We have t = 2 1 X n =1 ( & 1) n +1 n sin nt;t 2 ( & &;& ) : 1 step. We integrate termwise the series for the &rst time. We get t 2 2 = & 2 1 X n =1 ( & 1) n +1 n 2 cos nt + C 1 : Now let t = 0 = ) 0 = & 2 1 X n =1 ( & 1) n +1 n 2 + C 1 = ) C 1 = 2 ± & 2 12 = & 2 6 : So we have t 2 2 = & 2 1 X n =1 ( & 1) n +1 n 2 cos nt + & 2 6 : 2 step. We integrate termwise the series for the second time. We get t 3 6 = & 2 1 X n =1 ( & 1) n +1 n 3 sin nt + & 2 6 t + C 2 : Now let t = 0 = ) 0 = & 2 P 1 n =1 ( & 1) n +1 n 3 0 + 0 + C 2 = ) C 2 = 0 : We have t 3 6 = & 2 1 X n =1 ( & 1) n +1 n 3 sin nt + & 2 6 t: 3 step. We integrate termwise the series for the third time. We get t 4 24 = & 2 1 X n =1 ( & 1) n n 4 cos nt + & 2 12 t 2 + C 3 : Now let t = 0 = ) 0 = & 2 1 X n =1 ( & 1) n n 4 + 0 + C 3 = ) C 3 = 2 1 X n =1 ( & 1) n n 4 : So we have t 4 24 = & 2 t 2 12 & 2 1 X n =1 ( & 1) n n 4 cos nt + 2 1 X n =1 ( & 1) n n 4 : 5

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
4. Sec. 9.4: 3. We have x 00 + 3 x = F ( t ) ; where F ( t ) is the odd function of period 2 & with F ( t ) = 2 t;t 2 (0 ;& ) . We are looking for the sine series of F ( t ) = 2 t: b n = 2 & Z & 0 2 t sin ntdt = & 4 &n Z & 0 td cos nt = & 4 &n & t cos nt j & 0 & Z & 0 cos ntdt ± = & 4 &n & & cos n& & 1 n sin nt j & 0 ± = & 4 &n & & cos n& & 1 n (0 & 0) ± = & 4 n ( & 1) n : Thus F ( t ) = 4 1 X n =1 ( & 1) n +1 n sin nt: Now we are looking for the solution in the form x ( t ) = 1 X n =1 B n sin nt: Then x 0 ( t ) = 1 X n =1 nB n cos nt;x 00 ( t ) = & 1 X n =1 n 2 B n sin nt: So we get & 1 X n =1 n 2 B n sin nt + 3 1 X n =1 B n sin nt = 4 1 X n =1 ( & 1) n +1 n sin nt; that is, 3 B n & n 2 B n = 4 n ( & 1) n +1 = ) B n = 4 ( & 1) n n ( n 2 & 3) : Thus x sp ( t ) = 4 1 X n =1 ( & 1) n n ( n 2 & 3) sin nt: 6
5. Sec. 9.4: 7. We have x 00 + 9 x = F ( t ) ;

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## This note was uploaded on 01/26/2012 for the course MATH 285 taught by Professor Staff during the Fall '08 term at University of Illinois, Urbana Champaign.

### Page1 / 17

285hw10 - HW 10 1 Sec 9.3 5 We have f(t = 0 if t 2(0 1 f(t...

This preview shows document pages 1 - 8. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online